2016
DOI: 10.5171/2016.866941
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and pitfalls of training in a Lebanese manufacturing Company: a qualitative approach

Abstract: Not long ago, companies started investing millions of dollars on training and educating their workforce on new skills and improving prior skills. This increase in investment in training is mainly due to the rapid changes in technology and intense competition in the open market. However, this investment varied from one company to another. Training is a tool and a way to acquire new and different set of knowledge, skills and attitudes that are work related, and can have short and long term benefits for the emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The conceptualization of training in this way in the present study represents its main contribution. In general, the results obtained by the study were similar to the results of many other studies in the same context, which pointed out a significant as well as positive influence of training on organizational performance (Elnaga & Imran, 2013;Falola et al, 2014;Khan et al, 2011Khan et al, , 2017Kum et al, 2014;Percival et al, 2013;Saks & Burke-Smalley, 2014;Shaheen et al, 2013;Sherwani & Mohammed, 2015;Sultana et al, 2012;Talpur et al, 2016;Tangoukian et al, 2016;Umar et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The conceptualization of training in this way in the present study represents its main contribution. In general, the results obtained by the study were similar to the results of many other studies in the same context, which pointed out a significant as well as positive influence of training on organizational performance (Elnaga & Imran, 2013;Falola et al, 2014;Khan et al, 2011Khan et al, , 2017Kum et al, 2014;Percival et al, 2013;Saks & Burke-Smalley, 2014;Shaheen et al, 2013;Sherwani & Mohammed, 2015;Sultana et al, 2012;Talpur et al, 2016;Tangoukian et al, 2016;Umar et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Using a sample of the employees working at a Lebanese industrial company, Tangoukian et al (2016) conducted a study to examine the advantages and pitfalls of training and found that most of the departments in the company implement both internal and external training practices, despite the fact that employees prefer external training to internal training. In their review of research, the effect of training on organizational outcomes, such as human resource outcomes, performance outcomes, financial outcomes, and stock outcomes, Tharenou et al (2007) found that the strongest correlation was between training and organizational outco mes, such as organizational performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The study also found out that TD is another stage of training in the organisation (Altarawneh, 2005;Tangoukian et al, 2016). The significant ways of delivering training for optimal utilisation of site supervisors in construction firms are demonstration, group work (discussion), lectures and off-site training.…”
Section: Key Training Practice Indicators 2005mentioning
confidence: 94%
“…It is the process of acquiring new or additional skills and knowledge for improved performance on the present job (Siu and Lau, 1998). Armstrong (2006) emphasised that training should be a systematic procedural process with dimensions such as training needs analysis/assessment (Abdel-Maksoud and Saknidy, 2016; Tangoukian et al , 2016), training delivery (TD) (Mathis and Jackson, 2011; Tangoukian et al , 2016), training evaluation (TE) (Punia and Kant, 2013; Xiao et al , 2011) and training transfer (TT) (Bhatti et al , 2013; Punia and Kant, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation